2003
DOI: 10.1042/bj20021287
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and biochemical characterization of one Epsilon-class (GST-3) and ten Delta-class (GST-1) glutathione S-transferases from Drosophila melanogaster, and identification of additional nine members of the Epsilon class

Abstract: From the fruitfly, Drosophila melanogaster, ten members of the cluster of Delta-class glutathione S-transferases (GSTs; formerly denoted as Class I GSTs) and one member of the Epsilon-class cluster (formerly GST-3) have been cloned, expressed in Escherichia coli, and their catalytic properties have been determined. In addition, nine more members of the Epsilon cluster have been identified through bioinformatic analysis but not further characterized. Of the 11 expressed enzymes, seven accepted the lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(153 citation statements)
references
References 45 publications
4
146
1
2
Order By: Relevance
“…11) -are separated by considerable evolutionary distance. This situation resembles that found by us in the fruitfly Drosophila melanogaster where 4-HNE-metabolizing GSTs belong to at least two distinct classes Sawicki et al, 2003). The pattern depicted in Fig.…”
Section: Discussionmentioning
confidence: 49%
“…11) -are separated by considerable evolutionary distance. This situation resembles that found by us in the fruitfly Drosophila melanogaster where 4-HNE-metabolizing GSTs belong to at least two distinct classes Sawicki et al, 2003). The pattern depicted in Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Consistent with this scenario, we observed decreased JNK signaling and increased GST activity in the flies with Dpt overexpression and confirmed these changes by real-time PCR and enzyme activity assays, respectively. GST has been shown to play a role in antioxidant defense and has glutathione reductase activity in Drosophila (20,22,54). In particular, GstD3, which was up-regulated in the flies with Dpt overexpression, has also been shown to respond to dietary H 2 O 2 , and both GstD3 and GstE1 can metabolize 4-hydroxynonenal, a highly toxic aldehyde produced by lipid peroxidation in cells in response to oxidative stress (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated that paraquat treatment results in oxidative stress and induces the expression of several classes of GST genes in C. riparius . Similarly, cumene hydroperoxide and t-butylhydroperoxide are also widely used as model substances for studying the mechanism of cell injury resulting from oxidative stress (Sawicki et al 2003;Tang and Tu 1994). In the present study, paraquat, t-butylhydroperoxide and cumene hydroperoxide adsorbed to the filter disc may have induced oxidative stress in E. coli cells.…”
Section: Biochemical Characterization Of Accgsts1mentioning
confidence: 99%
“…The N-terminal domain (βαβαββα motif) containing the G-site and the C-terminal domain (all α-helical motifs) harboring the H-site are shown. The conserved Tyr at position 8 responsible for the stabilization of GSH is indicated oxidative stress (Arrese and Soulages 2010;Enayati et al 2005;Sawicki et al 2003). In addition, there is evidence that insect GSTs can detoxify many plant allelochemicals and synthetic insecticides (Li et al 2007).…”
Section: Tissue and Stage-specific Expression Profiles Of Accgsts1mentioning
confidence: 99%
See 1 more Smart Citation